2020
DOI: 10.1111/jch.13922
|View full text |Cite
|
Sign up to set email alerts
|

The slowdown in the reduction rate of premature mortality from cardiovascular diseases puts the Americas at risk of achieving SDG 3.4: A population trend analysis of 37 countries from 1990 to 2017

Abstract: Cardiovascular diseases (CVD) are leading causes of mortality and morbidity in the Americas, resulting in substantial negative economic and social impacts. This study describes the trends and inequalities of CVD burden in the Americas to guide programmatic interventions and health system responses. We examined the CVD burden trends by age, sex, and countries between 1990 and 2017 and quantified social inequalities in CVD burden across countries. In 2017, CVD accounted for 2 million deaths in the Americas, 29% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 30 publications
(32 reference statements)
1
31
0
13
Order By: Relevance
“…For instance, Martinez et al reported a descending trend of CVD YLD in the United States between 1990 and 2017. They also stated that rheumatic heart disease (RHD) had the sharpest downward slope among different types of cardiovascular diseases [ 11 ]. A worldwide study by Zimmerman et al indicated that the global YLD of congenital heart disease (CHD) had a relatively stable pattern between 1990 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Martinez et al reported a descending trend of CVD YLD in the United States between 1990 and 2017. They also stated that rheumatic heart disease (RHD) had the sharpest downward slope among different types of cardiovascular diseases [ 11 ]. A worldwide study by Zimmerman et al indicated that the global YLD of congenital heart disease (CHD) had a relatively stable pattern between 1990 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…National research has shown, as well as the present study, that the greatest temporal reduction has occurred in the rates of premature mortality due to cardiovascular diseases 10 . Authors suggest that the decline in mortality rates for this group of causes observed in Brazil is a result of smoking control measures and the expansion of access to primary care 27 , however studies have been pointing to a deceleration in the trajectory of reduction in mortality rates due to NCDs in Brazil 31,36 and even an increase after 2015 10 . The increase in the prevalence of risk factors such as hypertension and overweight, associated with the decrease in eating healthy foods and physical activity 27 , the fiscal austerity measures established in recent years in Brazil 37 and, currently, the health crisis imposed by the COVID-19 pandemic represent challenges to the progression of the trend of reducing mortality due to NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the number one underlying cause of death in the United States, directly contributing to almost 660,000 deaths in 2019 ( Roth et al, 2018 ). Despite continued advances in public health and medicine, recent data suggest that the decline of CVD mortality may have plateaued in the US ( Martinez et al, 2020 ; Wilmot et al, 2015 ). This stagnating decline in CVD mortality, rather than the rising “deaths of despair”, has been credited as the main reason why life expectancy in the US has stalled/declined in recent years ( Mehta et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%